A Corpus-Based Analysis of the Use of Singular Nouns by Pakistani Students in Higher Education - Mahmood Ahmad; Humaira Irfan; Muhammad Khalid (Corporum)
From its post-colonial history, English enjoys the status of an associated official language in Pakistan today. Since English is used in academic and non-academic settings, it is a natural question whether Pakistanis use English differently from standard British English, and what peculiarities they observe. Toanswer this question, this study analyzes 400 student essays in the Pakistani component of the International Corpus Network of Asian Learners of English. The analysis focuses on non-standard spelling, use of native words, countability, use of articles, numbers, noun combinations, collocations, and confusing nouns. The findings suggest that Pakistani English exhibits distinct features from standard British English in terms of spelling, word choice, and grammar. The study contributes to understanding the use of English in Pakistan and its status as a distinct variety.